Speeding in the slow lane: Phylogenetic comparative analyses reveal that not all human life history traits are exceptional. Issue 130 (May 2019) - Miller, Ian F.; Churchill, Steven E.; Nunn, Charles L.
Abstract: Humans are thought to exhibit an unusual suite of life history traits relative to other primates, with a longer lifespan, later age at first reproduction, and shorter interbirth interval. These assumptions are key components of popular hypotheses about human life history evolution, but they have yet to be investigated phylogenetically. We applied two phylogenetic comparative methods to investigate whether these human life history traits differ from expectations based on other primates: one fits and selects between Brownian and Ornstein-Uhlenbeck models of trait evolution; the other tests for phylogenetic outliers by predicting phenotypic characteristics based on trait covariation and phylogeny for a species of interest. We found that humans have exceptionally short interbirth intervals, long lifespans, and high birth masses. We failed to find evidence that humans have a delayed age at first reproduction relative to body mass or other covariates. Overall, our results support several previous assertions about the uniqueness of human life history characteristics and the importance of cooperative breeding and socioecology in human life history evolution. However, we suggest that several hypotheses about human life history need to be revised in light of our finding that humans do not have a delayed age at first reproduction.